2018
DOI: 10.3389/fmicb.2018.01250
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index Differences in the Gut Microbiota Are Gender Specific

Abstract: Background: The gut microbiota is increasingly recognized as playing an important role in the development of obesity, but the influence of gender remains elusive. Using a large cohort of Chinese adults, our study aimed to identify differences in gut microbiota as a function of body mass index (BMI) and investigate gender specific features within these differences.Methods: Five hundred fifty-one participants were categorized as underweight, normal, overweight, or obese, based on their BMI. Fecal microbiome comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
118
3
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(139 citation statements)
references
References 47 publications
14
118
3
4
Order By: Relevance
“…Here we report BMI-associated patterns in the adolescent gut microbiome composition and functions. The imbalance of Bacteroidetes to Firmicutes ratio has been reported in numerous studies (Duncan et al, 2008; Jumpertz et al 2011; Schwiertz et al 2011), and we previously reported that Bacteroidetes was enriched in obese adults comparing to lean subjects (Gao et al 2018). In the present data, no difference in the relative abundances of these two phyla upon comparison of obese and normal-weight adolescents, which is in agreement with findings of (Duncan et al 2008; Jumpertz et al 2011).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Here we report BMI-associated patterns in the adolescent gut microbiome composition and functions. The imbalance of Bacteroidetes to Firmicutes ratio has been reported in numerous studies (Duncan et al, 2008; Jumpertz et al 2011; Schwiertz et al 2011), and we previously reported that Bacteroidetes was enriched in obese adults comparing to lean subjects (Gao et al 2018). In the present data, no difference in the relative abundances of these two phyla upon comparison of obese and normal-weight adolescents, which is in agreement with findings of (Duncan et al 2008; Jumpertz et al 2011).…”
Section: Discussionsupporting
confidence: 53%
“…With the gut microbiota sequencing data of 516 Chinese adult, we previously found that BMI differences in the gut microbiome composition are gender specific (Gao et al 2018). Since age has also been reported as a confounding factor influencing the gut microbiome, and it is uncertain whether the gender differences discovered in adult people also exist in adolescents.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, gender did not impact on microbiome composition in our study. In studies in obese individuals, gender seems to cause taxonomic differences, whereas data on changes on alpha and beta diversity are still conflicting . In liver cirrhosis, gender differences have not been associated with changes in beta diversity so far.…”
Section: Discussionmentioning
confidence: 97%
“…In studies in obese individuals, gender seems to cause taxonomic differences, whereas data on changes on alpha and beta diversity are still conflicting. 73,74 In liver cirrhosis, gender differences have not been associated with changes in beta diversity so far. The male predominance in liver cirrhosis may be a reason for difficulties to detect consistent gender differences.…”
Section: Discussionmentioning
confidence: 98%